Project management toolbox - Milošević, Dragan; Martinelli, Russ J., 1959- (John Wiley & Sons, Inc., 2015)
Project Management ToolBox: Tools and Techniques for the Practicing Project Manager, Second Edition offers a succinct explanation of when, where, and how to use project management resources to enhance your work. With updated content that reflects key advances in the project management field, including planning, implementation, control, cost, and scheduling, this revised text offers added material that covers relevant topics, such as agility, change management, governance, reporting, and risk management. This comprehensive resource provides a contemporary set of tools, explaining each tool's purpose and intention, development, customization and variations, and benefits and disadvantages. Additionally, examples, tips, and milestone checks guide you through the application of these tools, helping you practically apply the information you learn.